Duck Plague Virus Negatively Regulates IFN Signaling to Promote Virus Proliferation via JNK Signaling Pathway - Wu, Liping; Tian, Bin; Wang, Mingshu; Cheng, Anchun; Jia, Renyong; Zhu, Dekang; Liu, Mafeng; Yang, Qiao; Wu, Ying; Huang, Juan; Zhao, XinXin; Chen, Shun; et al. (Frontiers in Immunology, 2022)
Duck plague virus (DPV), a member of the alphaherpesvirus subfamily, can cause severe damage and immunosuppression in ducks and geese in China. Since lacking an available cell model, the antiviral signal transduction pathways induction and regulation mechanisms related to DPV infection in duck cells are still enigmatic. Our previous study developed a monocyte/macrophages cell model, which has been applied to study innate immunity with DPV. In the present study, we compared and analyzed transcriptome associated with the DPV infection of CHv (virulent strain) and CHa (avirulent strain) at 48hpi based on the duck monocyte/macrophages cell model and RNA-seq technology. Differentially expressed genes (DEGs) analysis showed 2,909 and 2,438 genes altered in CHv and CHa infected cells compared with control cells. GO and KEGG signaling pathway analysis of DEGs were mainly involved in biological processes such as metabolic pathways, viral infectious diseases, immune system, and signal transduction. The CHv and CHa virus differentially regulated MAPK, NF-κB, and IFN signaling pathways based on transcriptome sequencing data and RT-qPCR results. The JNK inhibitor SP600125 enhanced the IFN signaling, but potentially reduced the VSV and DPV titers in the cell culture supernatant, indicating that JNK negatively regulates the IFN pathway and the inflammatory pathway to promote virus proliferation. The research results may provide promising information to understand the pathogenesis of DPV and provide a novel mechanism by which DPV modulates antiviral signaling and facilitate virus proliferation through hijacking the JNK pathway, which provides a new means for the prevention and control of DPV infection.